Clay mineral graphene oxide compound metal ion filter membrane and preparation method thereof
By combining serpentine nanosheets with graphene oxide, a serpentine/GO composite water treatment membrane was prepared, which solved the problems of complex preparation, high cost and adsorbent toxicity in the prior art, and achieved efficient removal and reusability of heavy metal ions.
Patent Information
- Application Number
- CN202411545627.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-28
AI Technical Summary
The existing water treatment membrane preparation process is complex, the production cost is high, and many chemically synthesized adsorbents are toxic, which may lead to secondary pollution of the water body and make it difficult to effectively remove heavy metal ions in the water.
By combining serpentine nanosheets with graphene oxide (GO), an ultra-thin serpentine/GO composite water treatment membrane was prepared, and the huge specific surface area and negatively charged functional groups were used to achieve efficient adsorption of heavy metal ions.
The efficient removal of heavy metal ions is achieved, especially the removal rate of cadmium and lead ions reaches 100%, and the film has good reusability and avoids secondary pollution of water.
Smart Images

Figure BDA0005113704170000041 
Figure HDA0005113704180000011 
Figure HDA0005113704180000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane technology, and in particular relates to a clay mineral graphene oxide composite metal ion filter membrane and a preparation method thereof. Background Art
[0002] The increasingly serious global water ecological pollution has become one of the most important environmental problems. This pollution mainly comes from multiple aspects, such as industrial wastewater, domestic wastewater, agricultural pollution, etc., which have caused serious damage to marine and freshwater ecosystems. Among all types of water pollutants, toxic heavy metal ions (HMs) cause the greatest pollution hazards. Heavy metal ions are widely present in water systems (such as soil, sediment, surface water and groundwater). Among these heavy metal ions, cadmium (Cd) and lead (Pb) ions have attracted great attention from researchers due to their high toxicity and wide distribution. Even if these heavy metal ions are in very low concentrations in water, they may cause serious diseases in organisms. Therefore, it is of great significance to capture and remove heavy metal ions from natural water and engineering wastewater. Various advanced technologies have been developed to remove heavy metal ions from aquatic environments, such as chemical precipitation, electrochemical reduction, ion exchange, membrane filtration and adsorption. Among them, the method of combining membrane filtration and adsorption is a simple, economical and effective strategy for removing heavy metal ions from aquatic environments. At present, it is found that most of the filter membranes on the market have complicated preparation processes and high production costs, and many chemically synthesized adsorbents themselves have certain toxicity and will cause secondary pollution of water bodies. Therefore, the preparation of environmentally friendly, low-cost, and easily recyclable water treatment membranes is the key to effectively control heavy metal pollution. Summary of the invention
[0003] Studies have shown that in the natural environment, heavy metal ions present in the soil are firmly adsorbed by the surface of serpentine, thereby regulating the geochemical behavior of heavy metal ions and affecting their mobility in the aquatic environment. Therefore, serpentine has become an economical and efficient heavy metal ion adsorption material. However, natural serpentine is a layered clay mineral composed of alternating Si-O tetrahedrons and Mg-OH octahedron planes, with a small specific surface area and very limited adsorption of metal ions. As a new type of nanomaterial, graphene oxide (GO) has a very large specific surface area due to its layered structure, which means that it has a large surface area that can contact heavy metal ions, thereby increasing the adsorption efficiency. If the adsorption effect of serpentine can be combined with the huge surface area of GO, it can play a good adsorption role; secondly, the surface of GO contains a large number of oxygen-containing functional groups such as epoxy groups, hydroxyl groups, and carboxyl groups. These functional groups contain lone pairs of electrons, making GO negatively charged, which can form a complex with clay minerals containing metal ions through electrostatic adsorption. In view of this situation, the present invention proposes to prepare serpentine nanosheets using serpentine, use GO as a template to prepare an ultrathin serpentine / GO composite, and use the composite to prepare a water treatment membrane for adsorbing heavy metal ions in water.
[0004] In order to achieve the above purpose, the present invention mainly uses serpentine powder, isopropanol, cadmium nitrate tetrahydrate, lead nitrate, sodium nitrate, GO solution, polypropylene microporous filter membrane and other reagents as raw materials, peels off serpentine nanosheets through a microwave reactor, and composites them with GO to prepare a serpentine / GO composite water treatment membrane.
[0005] The specific steps of the preparation method are as follows:
[0006] Step 1: Preparation of serpentine nanosheets. Serpentine powder is dispersed in isopropanol and exfoliated using a water bath ultrasonic generator. After ultrasonication for a period of time, the obtained dispersion is centrifuged at a low speed for a period of time, the supernatant is taken, and the separated supernatant is centrifuged at a high speed for a period of time to obtain serpentine nano-sedimentation sheets, and the sedimentation sheets are precipitated and dried in a vacuum drying oven for later use.
[0007] Step 2: Preparation of serpentine / GO composite. Take the serpentine nanosheets prepared in the first step and add a certain amount of isopropanol to dilute to a certain concentration. Take a certain amount of GO aqueous solution, add the serpentine isopropanol solution dropwise to the GO solution at a certain temperature, and prepare the serpentine / GO composite solution after ultrasonic treatment of the mixed solution for a period of time. This solution is the membrane-making solution for preparing the composite membrane.
[0008] Step 3: Preparation of serpentine / GO composite membrane. Install the polypropylene microporous filter membrane on the glass sand core funnel, slowly pour a certain amount of ultrasonic membrane-making solution into the funnel, vacuum filter, and dry under natural conditions to obtain the serpentine / GO composite membrane.
[0009] In the present invention, in the preparation process of the first step, the isopropanol solution of serpentine is 2-5 mg / mL, the water bath ultrasonic temperature is room temperature 60°C, the time is 6-12 hours, the low speed is 2500-4000 rpm, the time is 10-50 minutes, the high speed is 12000-20000 rpm, the time is 1-2 hours, and the vacuum drying temperature is 60-100°C, and the time is 4-10 hours.
[0010] In the present invention, in the second step of the preparation process, the concentration of the serpentine nanosheet solution is 1-5 mg / mL, the concentration of the GO solution is 1-5 mg / mL, and the volume ratio of the serpentine nanosheet solution to the GO solution is 0.5-2. The ultrasonic temperature of the mixed solution is room temperature 60°C, and the ultrasonic time is 30 minutes to 3 hours.
[0011] In the present invention, in the preparation process of the third step, a polypropylene microporous filter membrane with a diameter of 50 mm and a pore size of 0.22 μm is installed on a glass sand core funnel, and the amount of membrane-making liquid is 10-20 ml. The ultrasonic membrane-making liquid is slowly poured into the funnel, filtered for 30-60 minutes, and dried under natural conditions to obtain a serpentine / GO composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0013] Figure 1 It is the external standard curve of cadmium ion (Cd) and is determined by atomic absorption spectrometry.
[0014] Figure 2 Comparison of the volumes of serpentine / GO composite and serpentine powder of the same mass.
[0015] Figure 3 It is the external standard curve of lead ion (Pb) and is determined by atomic absorption spectrometry. DETAILED DESCRIPTION
[0016] The following examples further illustrate the preparation method of clay mineral modified GO membrane and its treatment performance for lead and cadmium ions.
[0017] The reagents used in the present invention, such as serpentine powder, isopropanol, cadmium nitrate tetrahydrate, lead nitrate, sodium nitrate, sodium hydroxide, nitric acid solution and the like, were purchased from Chengdu Kelong Reagent Co., Ltd.
[0018] The ultrasonic instrument used for serpentine powder exfoliation is UH3000 / 4000-AIO ultrasonic processor.
[0019] The centrifuge used for separation of serpentine nanosheets was a TG20G desktop high-speed centrifuge.
[0020] The quantitative analysis of lead and chromium ion solutions was tested using an AA-1800F atomic absorption spectrometer.
[0021] Example 1 Preparation of serpentine / GO composite membrane
[0022] The serpentine blocks were crushed into powder, and a certain amount of isopropanol was added to prepare a 3mg / mL solution. The solution was exfoliated and ultrasonicated in a water bath ultrasonic generator. After 6 hours, the obtained dispersion was centrifuged at 3000rpm for 15 minutes, and the upper clear liquid was poured out, and the lower precipitate was discarded to remove the unpeeled serpentine powder. The upper clear liquid was centrifuged at 12,000rpm for 60 minutes to settle the two-dimensional serpentine nanosheets in the clear liquid, and the upper liquid was poured out. The serpentine nanosheets obtained in the lower layer were dried in a vacuum oven at 50°C for 4 hours, and the residual solvent was completely evaporated to obtain solid serpentine nanosheets. Take the serpentine nanosheets, add isopropanol to prepare a 2mg / mL solution, and ultrasonicate at 40°C in an ultrasonic oscillator for 5 minutes to obtain a light yellow liquid. 10ml of this light yellow solution was added dropwise to 10ml of GO dispersion with a concentration of 2mg / mL, and the mixed solution was ultrasonicated for 60 minutes to obtain a serpentine / GO composite solution. A polypropylene microporous filter membrane with a diameter of 50 mm and a pore size of 0.22 um was installed on a glass sand core funnel, and the membrane-making solution after ultrasound was slowly poured into the funnel. The membrane was filtered for 30 minutes and dried under natural conditions to obtain a serpentine / GO composite membrane.
[0023] Comparative Example 1 Preparation of GO membrane
[0024] 10 mL of 2 mg / L GO solution and 10 mL of pure water were fully mixed to prepare 20 mL of membrane solution, and the membrane solution was ultrasonicated for 30 minutes before use. A polypropylene microporous filter membrane with a diameter of 50 mm and a pore size of 0.22 μm was installed on a glass sand core funnel, and the ultrasonic membrane solution was slowly poured into the funnel, filtered for 35 minutes, and dried under natural conditions to obtain a GO membrane.
[0025] Comparative Example 2 Preparation of serpentine film
[0026] Take a certain amount of serpentine and crush it into serpentine powder, add 20ml isopropanol to make a 2mg / mL solution, ultrasonicate it in an ultrasonic oscillator at 40℃ for 5 minutes to obtain a yellow turbid liquid. Install a polypropylene microporous filter membrane with a diameter of 50mm and a pore size of 0.22um on a glass sand core funnel, slowly pour the ultrasonicated serpentine solution into the funnel and filter it until no solution drips out, and dry it under natural conditions to obtain a serpentine filter membrane.
[0027] Test Example 1
[0028] First, prepare 50, 100, 150, 200, and 250 ppm cadmium (Cd) ion standard liquids to make an external standard curve for Cd ions (e.g. Figure 1 ). In order to better reflect the adsorption effect of serpentine / GO composites in the natural environment, this paper selects the typical aquatic environment pH value (5.5) to study the adsorption process of metal ions to avoid the uncertainty caused by heavy metal ion precipitation. An appropriate amount of Cd(NO3)2·4H2O was dissolved in pure water, and the pH was adjusted to 5.5 with nitric acid to prepare a solution with a Cd ion content of 200 mg / L. A clean and dry 150mL ground-mouth conical flask was used as a liquid receiver, and 25 ml of the above solution was transferred to a glass sand core funnel equipped with serpentine / GO composite membrane, serpentine filter membrane, and GO membrane for filtration. After the filtration, the absorbance of Cd ions before and after separation was measured on the atomic absorption spectrum, and compared with the standard curve to obtain the concentration of the solution after interception. The retention rate is calculated according to the formula, where C0 is the initial concentration of the metal ion (mg / L), C f is the concentration of metal ions after filtration (mg / L).
[0029]
[0030] The test found that almost no Cd ions were detected after passing through the serpentine / GO composite membrane, with a removal rate of 100%; the Cd ion concentration passing through the serpentine filter membrane was 80ppm, with a removal rate of 60%; the Cd ion concentration passing through the GO membrane was 116ppm, with a removal rate of 42%. The differences between the three different filter membranes are very obvious, which may be because the two-dimensional serpentine nanosheets have a Janus structure, and the adsorption of metal ions shows the characteristics of surface adsorption, but the inherent stacking structure inside the serpentine makes the exposed adsorption sites less, limiting the full utilization of its complete surface in adsorption, especially the internal voids, so the removal rate of Cd ions is not high. GO, which is composed of a single layer of carbon atoms, has a unique six-membered carbon ring conjugated large π bond structure that gives it an extremely high specific surface area. Although there are a large number of oxygen-containing functional groups on the surface of GO, which can adsorb metal ions, the interaction between oxygen-containing functional groups and metals is weaker than the complexation between serpentine and metal ions, so the adsorption of GO is lower than that of serpentine. The serpentine / GO composite membrane is made by preparing serpentine into nanosheets. The nano-shaped serpentine fully exposes its adsorption sites. Since serpentine contains metal ions, the nanosheets show positive charge. The positively charged nanosheets are attached to the negatively charged GO with a huge specific surface area through ultrasound. This not only fully exposes the adsorption sites of serpentine, but also enables the oxidized groups of GO to play an adsorption role, achieving an adsorption effect of one plus one greater than two, so it has a strong adsorption capacity.
[0031] The composite prepared with GO as template has a very high specific surface area due to the large π-bond structure of the six-membered carbon ring conjugation, which fully exposes the Janus structure of serpentine. The construction of ultra-thin composite film can increase the contact between active sites and target molecules in pollutant environments. The volume of serpentine / GO and serpentine powder of the same mass is significantly different, such as Figure 2 .
[0032] The desorption experiment of the filter membrane is to soak the membrane treated with Cd ions in 100ml of dilute hydrochloric acid (0.2mol / L) for 10 minutes and then filter it, and wash the filter membrane with pure water under the condition of filtration until it is neutral. After the filter membrane is dried, it is used for the next adsorption of Cd ions. This method is used to repeatedly treat the Cd ion solution for 5 times. No Cd ions are detected in the filtrate through the serpentine / GO composite membrane, and the 5th time through the serpentine filter membrane is about 5% lower than the initial treatment. The decrease through the GO membrane is the largest. After the GO membrane repeatedly treats the Cd ion solution for 2 times, it can hardly absorb Cd ions. This may be because the adsorption of metal ions by serpentine depends on two adsorption modes: Mg–OH (monodentate inner sphere complexation) and Si–O (outer sphere complexation). Therefore, under strong acidic conditions (pH<2.8), the complexation is greatly weakened, and the adsorption capacity of serpentine powder for Cd ions is greatly reduced. This phenomenon makes the composite membrane reusable. The interaction with GO is only the electrostatic adsorption between the oxidized groups and the metal. The effect of acid on electrostatic adsorption is smaller than that on complexation. Therefore, the repeatability of GO's adsorption of cadmium (II) ions is not strong.
[0033] Test Example 2
[0034] Prepare 50, 100, 150, 200, 250 ppm lead (Pb) ion standard liquid and make an external standard curve of Pb ion, such as Figure 3 An appropriate amount of Pb(NO3)2 was dissolved in deionized water, and the initial pH value of the Pb solution was adjusted to 5.5.
[0035] A solution with a Pb ion content of 200 mg / L was prepared. A clean and dry 150 mL ground-mouth conical flask was used as a liquid receiver. 25 ml of the above solution was transferred to a glass sand core funnel equipped with a serpentine / GO composite membrane, a serpentine filter membrane, and a GO membrane for filtration. After the filtration, the absorbance of the Pb ions before and after separation was measured on an atomic absorption spectrometer and compared with a standard curve (such as Figure 3 ) were compared to obtain the concentration of the solution after interception.
[0036] The test found that after passing through the serpentine / GO composite membrane, almost no cadmium ions were detected, with a removal rate of 100%; the concentration of Pb ions passing through the serpentine filter membrane was 96ppm, with a removal rate of 52%; the concentration of Pb ions passing through the GO membrane was 120ppm, with a removal rate of 40%. The effects of the three different filter membranes on Pb ions were similar to those on Cd ions. Except for the low removal rate of the serpentine filter membrane, the removal rates of the other two filter membranes were not much different. The main reason for the large difference in the serpentine filter membrane is that the ion radius of Cd is smaller and the charge density is larger, and the electrostatic attraction generated by serpentine is stronger than that of Cd, so the removal rate of Pb ions is higher than that of Cd ions. The desorption experiment of the filter membrane is to soak the membrane treated with Pb ions in 100ml of dilute hydrochloric acid (0.2mol / L) for 10 minutes and then filter it, and wash the filter membrane with pure water under the condition of filtration until it is neutral. After the filter membrane is dried, it is used for the next adsorption of Pb ions. The results and mechanism are similar to those of Cd.
Claims
1. A clay mineral graphene oxide composite metal ion filter membrane and a preparation method thereof, which is realized by ultrasonic stripping and complexation reaction, characterized in that: The steps include: Step 1: Preparation of serpentine nanosheets: serpentine powder is dispersed in isopropanol and exfoliated using a water bath ultrasonic generator. After ultrasonication for a period of time, the obtained dispersion is centrifuged at a low speed for a period of time, the supernatant is taken, and then centrifuged at a high speed for a period of time to obtain serpentine nano-sedimentation sheets, and the precipitate is dried in a vacuum drying oven for later use; Step 2: Preparation of serpentine / graphene oxide (GO) composites. Take the serpentine nanosheets prepared in the first step, add a certain amount of isopropanol to dilute to a certain concentration, take a certain amount of GO aqueous solution, add the serpentine isopropanol solution dropwise into the GO solution at a certain temperature, and prepare a serpentine / GO composite solution after ultrasonic treatment of the mixed solution for a period of time. This solution is the membrane-making solution for preparing the composite membrane; Step 3: Preparation of serpentine / GO composite membrane. Install the polypropylene microporous filter membrane on the glass sand core funnel, slowly pour a certain amount of ultrasonic membrane-making solution into the funnel, vacuum filter, and dry under natural conditions to obtain the serpentine / GO composite membrane.
2. According to claim 1, in the preparation process of the first step, the isopropanol solution of serpentine is 2-5 mg / mL, the water bath ultrasonic temperature is room temperature-60°C, the time is 6-12 hours, the low speed is 2500-4000rpm, the time is 10-50 minutes, the high speed is 12000-20000rpm, the time is 1-2 hours, and the vacuum drying temperature is 60-100°C, and the time is 4-10 hours.
3. According to claim 1, in the second step of the preparation process, the concentration of the serpentine nanosheet solution is 1-5 mg / mL, the concentration of the GO solution is 1-5 mg / mL, and the volume ratio of the serpentine nanosheet solution to the GO solution is 0.5-2. The ultrasonic temperature of the mixed solution is room temperature-60°C, and the ultrasonic time is 30 minutes-3 hours.
4. According to the preparation process of the third step of claim 1, a polypropylene microporous filter membrane with a diameter of 50 mm and a pore size of 0.22 μm is installed on a glass sand core funnel, and the amount of membrane-making liquid is 10-20 ml. The ultrasonic membrane-making liquid is slowly poured into the funnel, filtered for 30-60 minutes, and dried under natural conditions to obtain a serpentine / GO composite membrane.